Heat transfer study on finned tube heat exchanger using CFD. Issue 3 (17th February 2021) - Rajeshkumar, M.; Logesh, K.; Thangaraj, M.; Govindan, S.
ABSTRACT: Improving the performance of heat exchangers is the primary objective of this study. Increasing the surface area of the heat exchanger will increase the heat transfer rate enormously. Extended surfaces with innovative shape and material enhance the heat exchanger performances. CFD analysis provides the multidirectional approximation to identify the better heat exchanger in the view of sizing and rating. In this paper, the performance of Tube heat exchanger is studied with a different arrangement of Fins using CFD. This Analysis is done for an existing tube heat exchanger with the specified conditions of the inlet flow and the heat exchange between the three different nozzles is modelled through ANSYS. Heat generated in the process of CFD formulation to be helped to compare mathematical and analytical results. Temperature distribution process much need to heat flow generating process.